1972
DOI: 10.1177/070674377201700104
|View full text |Cite
|
Sign up to set email alerts
|

Survival Rates and Causes of Death in Geriatric Psychiatric Patients: A Six-Year Follow-up Study.

Abstract: This is a six-year follow-up study of one hundred and thirty geriatric psychiatric patients admitted to the Winnipeg Psychiatric Institute in 1964. The main findings were: 1) Survival rates were lowest in senile patients with arteriosclerotic dementias. Those with other dementias and confusional states and male paranoid patients did somewhat better. Female paranoid patients and those with affective disorders did not differ significantly from the general population. 2) The survival rate of patients with senil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
15
0

Year Published

1976
1976
2004
2004

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 8 publications
3
15
0
Order By: Relevance
“…The observed high mortality from pneumonia in our patients with Alzheimer's disease agrees with prior mortarity studies of elderly persons with dementia; the most common cause of death among patients with senile dementia was also pneumonia in a six-year follow-up study of elderly psychiatric patients (Varsamis et al, 1972) as well as in Scottish death certi®cate data concerning patients with presenile Alzheimer's disease (Thomas et al, 1997). Further, death from pneumonia was three-times as common among older individuals with dementia as in patients of a similar age who had other forms of psychiatric illness (Kay, 1962).…”
Section: Discussionsupporting
confidence: 89%
“…The observed high mortality from pneumonia in our patients with Alzheimer's disease agrees with prior mortarity studies of elderly persons with dementia; the most common cause of death among patients with senile dementia was also pneumonia in a six-year follow-up study of elderly psychiatric patients (Varsamis et al, 1972) as well as in Scottish death certi®cate data concerning patients with presenile Alzheimer's disease (Thomas et al, 1997). Further, death from pneumonia was three-times as common among older individuals with dementia as in patients of a similar age who had other forms of psychiatric illness (Kay, 1962).…”
Section: Discussionsupporting
confidence: 89%
“…Roth found that after six months, 33Vo of the arteriosclerotic cases were dead, and 59Vo of the senile dementia patients. Many subsequent studies have confirmed this picture (Kay, 1962;Varsamis et al, 1972).…”
Section: Natural Historysupporting
confidence: 53%
“…Although the symptoms of delirium typically resolve within 10−12 days and the majority of patients have full recovery, delirium is associated with increased morbidity and mortality 2 , 3 and can progress to stupor, coma, seizures or death. In particular, elderly patients are less likely to recover fully and can experience persistent cognitive deficits.…”
Section: Introductionmentioning
confidence: 99%